Der quartäre Klimawandel - System oder geschichtliches Ereignis? Überlegungen zur geographischen Methode am Beispiel von Eiszeittheorien - Kuhle, Matthias; Kuhle, Sabine (ERDKUNDE, 1997)
Taking the Pleistocene Ice Age as a paradigm for the explanation of historical climatic changes, there are two methodical options: they can be taken a) as a climatic system, the immanent structure of which creates a regularly repeated glacial-/interglacial-cycle within time; or b) as a historical event where every time slice is characterized by new, discordant junctions of structural elements and their successive functional change. Consequently, the characteristics of the Ice Age are polyhistoric and cannot be attributed to a simple causal machinery. Option a) proposes an identity of the system parallel to the time-axis, while b) regards this as irrational, thus joining the evolutionary methodical concept of Biology and Human History.